Exploring Iron Oxide Nanoparticles Innovations and Applications in Cancer Therapy - Roy, Megha; Sheikh, Mujibullah; Telange, Darshan (International Journal of Pharmaceutical Investigation, 2025)
Iron Oxide Nanoparticles (IONPs) are exciting technology in cancer therapy that represents agents with a unique combination of super paramagnetism, biocompatibility and the capability for surface functionalization toward targeted applications. The following review describes the current innovations and various applications of IONPs against cancer, dealing with their roles in targeted drug delivery, hyperthermia and imaging. IONPs can be synthesized by various chemical and physical methods, for instance, co-precipitation or thermal decomposition. Characterization techniques for their structural and magnetic properties include transmission electron microscopy and vibrating sample magnetometry. IONPs allow for targeted drug delivery by the release of therapeutic agents at a specific location, reducing systemic toxicity. In magnetic hyperthermia applications, they exploit the ability to produce heat during the alternating magnetic field exposure and induce apoptosis in tumor cells. Moreover, IONPs serve as magnetic resonance contrast imaging agents, enhancing tumors' imaging. Even with the great promise of IONPs, concerns about toxicity and biocompatibility and scalable production methods have yet to be realized. Combination therapies interlacing IONPs with other therapeutic modalities, as well as further research into their elicited immunomodulatory effects, are some of the future perspectives that have been outlined. Taken together, advancements in IONP technology herald a new frontier in cancer therapy, offering innovative strategies to improve treatment efficacy and the lives of patients.
Keywords: Cancer Therapy; Hyperthermia Treatment; Iron Oxide Nanoparticles; Photodynamic Therapy; Photothermal Therapy; Superparamagnetic Iron Oxide Nanoparticles; Targeted Drug Delivery